Ongoing Mental Health Concerns in Post-3/11 Japan - Adam Karz (Ubiquity Press, 2014)
Background: The triple disaster that struck the Tohoku region on March 11, 2011, has had massive psychiatric, social, and physical effects on the people of Japan. A staggering loss of life and property, as well as an ongoing nuclear disaster, has dramatically affected the ability of the country to recover. Objective: In an effort to better understand the current social, health, and mental health needs of the region affected by the disaster and to share lessons from 9/11, a group of 9/11 survivors and doctors from the Icahn School of Medicine at Mount Sinai traveled to sites throughout the Fukushima, Miyagi, and Iwate prefectures. Methods: A qualitative analysis was performed on transcripts of the cultural and medical exchanges, which occurred on this trip to identify relevant themes about the problems confronting the recovery effort almost 3 years after the disaster. Findings: Significant themes that emerged included a crippling radiation anxiety, a considerable stigma toward addressing mental health care, and a shortage of mental health care throughout the region, as well as ongoing psychiatric symptoms such as insomnia, anxiety, and alcohol misuse. Conclusions: These issues continue to complicate the recovery effort but suggest avenues for future interventions.